2012
DOI: 10.1111/j.1708-8208.2010.00299.x
|View full text |Cite
|
Sign up to set email alerts
|

The Profile of Inflammatory Cytokines in Gingival Crevicular Fluid around Healthy Osseointegrated Implants

Abstract: Despite gingival tissue health and scarce plaque accumulation, the profile of inflammatory cytokines in implant crevicular fluid was distinctive of an innate immune response and in higher concentration than in teeth. Other than bacterial stimulus, intrinsic factors related to implants may account for more cytokine production than teeth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
52
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(68 citation statements)
references
References 25 publications
8
52
1
Order By: Relevance
“…The authors found low but measureable levels of proinflammatory cytokines in PICF after implant placement, which is consistent with previous data on inflammatory responses after implant placement 14,23,41 . Notably, the data of very low levels of IL‐8 and IL‐1α in PICF and GCF at the 1‐year follow‐up are in agreement with the findings of a previous report 34 showing low concentrations of IL‐1β in PICF.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The authors found low but measureable levels of proinflammatory cytokines in PICF after implant placement, which is consistent with previous data on inflammatory responses after implant placement 14,23,41 . Notably, the data of very low levels of IL‐8 and IL‐1α in PICF and GCF at the 1‐year follow‐up are in agreement with the findings of a previous report 34 showing low concentrations of IL‐1β in PICF.…”
Section: Discussionsupporting
confidence: 90%
“…The maintenance of bone volume is regulated by balanced processes of apposition and resorption; these processes are controlled in part by the local production of cytokines, small polypeptides with a wide range of pro‐inflammatory, metabolic, and immunomodulatory properties 11,12 . For example, interleukin (IL)‐1β and tumor necrosis factor (TNF)‐α are potent pro‐inflammatory cytokines 11 that are involved in the pathogenesis of many chronic inflammatory diseases (e.g., peri‐implantitis 13 ) and are present in peri‐implant crevicular fluid (PICF) 14‐17 . The titanium surfaces of dental implants can stimulate peripheral blood mononuclear cells to secrete IL‐1β, TNF‐α, 18 IL‐1, IL‐6, and IL‐18 19 in vitro, indicating that dental implants are not biochemically inert.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Socransky et al 14 stated that mainly anaerobic Gram‐negative bacterial species such as Tannerella forsythia ( Tf ), Treponema denticola ( Td ), and Porphyromonas gingivalis ( Pg ) are associated with periodontal destruction. To date, levels of key biologic mediators in gingival crevicular fluid (GCF) and PICF samples have been comparatively investigated in few studies 15 , 16 . It was hypothesized that possible differences in cytokine content and/or bacterial species between healthy and diseased sites may reveal similar factors acting in the pathogenesis of periodontitis and peri‐implantitis.…”
mentioning
confidence: 99%
“…Lower levels of inflammatory infiltrate and cytokine expression have been observed in tissue adjacent to ceramics when compared to titanium . In contrast, production of pro‐inflammatory cytokines (especially IL‐1β and TNF‐α) around titanium implants was observed in higher concentrations than in teeth despite gingival tissue health and scarce plaque accumulation . Nonetheless, the clinical impact of these phenomena remains unknown.…”
Section: Introductionmentioning
confidence: 99%